Pengembangan Virtual Assistant (Chatbot) Bebrbasis NLP (Natural Language Processing) Untuk Portal Informasi Terpadu Pariwisata Tasikmalaya - Hidayat, Cepi Rahmat; Sumaryana, Yusuf; Syahrul Anwar, Dede; Fadilah, Ai Linda Nurahmah; Saputra, Muhammad Randika (LPPM Universitas Potensi Utama, 2025)
Tasikmalaya, known for its natural beauty and cultural richness, has great potential as an attractive tourist destination. One of the main challenges faced is how to convey accurate and integrated information to tourists quickly and easily so that it can be used to improve marketing strategies and destination development. This study aims to develop a virtual assistant (chatbot) based on Natural Language Processing (NLP) for the integrated Tasikmalaya tourism information portal in handling high volumes of questions simultaneously, reducing the workload of human staff and optimizing the service process. The research method uses a waterfall model by applying the NLP approach. The final result of this study is to produce a virtual assistant (chatbot) application that allows users to get information related to Tasikmalaya tourism destinations in a more flexible way. The application was tested using the black box method and showed that the application ran as expected while the SUS test carried out obtained a final score of 72.30 in the Good category.